The Socioeconomic History of Orang Kanaq of Johor - Mahani Musa (Kajian Malaysia, 2011)
The Orang Kanaq are the Orang Asli group that can only be found in Kota Tinggi, Johor. Originally from Sumatra, the group had a long history as vassals for Johor rulers before losing their influence due to economic and political changes that have occurred in the Riau-Lingga archipelago since the 18th century. This paper examines the early history of the Orang Kanaq, the factors that led to their decline prior to the arrival of European powers, and their migration to Kota Tinggi. Since the end of the 19th century, patron-client ties in modernising Johor have become less important; this has pushed the Orang Kanaq to the margins of society. Forced resettlements during the Emergency (1948–60) and efforts to ''modernise'' them economically and socially have proven to be challenging tasks for both the government and the Kanaq themselves.